3D containment modeling of PWR-KWU Trillo NPP with the GOTHIC code. (November 2019) - Fernández-Cosials, Kevin; Estévez-Albuja, Samanta; Jiménez, Gonzalo; Bocanegra, Rafael; Vázquez-Rodríguez, Carlos; Rey, Luis; Martínez-Murillo, Juan Carlos
Highlights: A method to create complex containments 3D models with porous CFDs is presented. The methodology uses the inverse meshing process; the mesh is firstly created, and then the geometry is adapted. A sensitivity analysis of modeling simplifications is presented, showing robustness of the model and method. Abstract: Containment safety analysis is a field in expansion given the complex phenomenology developed during an accident, and the recent code capabilities improvement. In this paper, a modeling strategy to create complex containments with porous CFDs in a single control volume is presented. This methodology involves using solely Computer Aided Design (CAD) tools, to manage the geometrical model, instead of using the GOTHIC code pre-processor interface. This methodology is applied to Trillo NPP (KWU 3 loops) where a LBLOCA is simulated to illustrate its capabilities. The results are compared against a Lumped Parameters model obtaining similar average values. Finally, a sensitivity analysis is made to quantify the influence of the modeling simplifications showing a small dependence. This implies that this modeling strategy is able to recreate models accurately, with an affordable computational cost, and with a time saving improvement, which nowadays is the main bottleneck for 3D containment models.